Engaging, leading and improving at the Northern Ireland Faculty of Medical Leadership and Management (FMLM) conference. Issue 4 (27th October 2017) - Curran, Judy; Doherty, Rachel; Donaghy, Gráinne; Gardiner, Keith
Abstract : This article is a review of the Northern Ireland Faculty of Medical Leadership and Management (FMLM) conference, which took place on 9 March 2017 in Riddel Hall, Belfast. The conference programme included a number of inspiring and motivational keynote talks and workshops that embedded the theme of 'Engaging, Leading and Improving' throughout. This article summarises the main points from the keynote speakers and workshops. It also details the key learning points arising from the day as highlighted by delegate feedback.